2010
DOI: 10.2353/ajpath.2010.090504
|View full text |Cite
|
Sign up to set email alerts
|

Plasmepsin 4-Deficient Plasmodium berghei Are Virulence Attenuated and Induce Protective Immunity against Experimental Malaria

Abstract: Plasmodium parasites lacking plasmepsin 4 (PM4), an aspartic protease that functions in the lysosomal compartment and contributes to hemoglobin digestion , have only a modest decrease in the asexual blood-stage growth rate; however , PM4 deficiency in the rodent malaria parasite Plasmodium berghei results in significantly less virulence than that for the parental parasite. P. berghei ⌬pm4 parasites failed to induce experimental cerebral malaria (ECM) in ECMsusceptible mice , and ECM-resistant mice were able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
137
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(139 citation statements)
references
References 48 publications
2
137
0
Order By: Relevance
“…The reporter Pb ANKA parasite line Pb GFP-Luc ama1 (1037m1f1m1cl1) expresses a fusion protein of GFP (mutant3) and fi refl y luciferase (LUC-IAV) under the schizont-specifi c ama-1 promoter and is SM free [ 16 ]. The reporter cassette is integrated into the neutral 230p locus (PBANKA_030600).…”
Section: Standard Parasites Lines Used For Generation Transgenic Paramentioning
confidence: 99%
“…The reporter Pb ANKA parasite line Pb GFP-Luc ama1 (1037m1f1m1cl1) expresses a fusion protein of GFP (mutant3) and fi refl y luciferase (LUC-IAV) under the schizont-specifi c ama-1 promoter and is SM free [ 16 ]. The reporter cassette is integrated into the neutral 230p locus (PBANKA_030600).…”
Section: Standard Parasites Lines Used For Generation Transgenic Paramentioning
confidence: 99%
“…First, in human malaria, the expression of several specific PfEMP1 proteins promoted cytoadherence to brain endothelial cells and correlated with the severity of cerebral malaria (12,13), suggesting that these proteins constitute a major virulence factor for cerebral malaria. Second, in rodents, the plasmepsin-4 (pm4) gene, encoding an aspartic protease involved in hemoglobin digestion, was shown to be implicated in experimental cerebral malaria (ECM) (14,15). Finally, several studies also reported a crucial role for ICAM-1 in malaria pathogenesis, and notably, ICAM-1-deficient mice are protected from ECM (16).…”
mentioning
confidence: 99%
“…The P. berghei ANKA reporter line 1037cl1 (ANKA-GFPLucschiz [Luc]; mutant RMgm-32) (http://www.pberghei.eu), which contains the gfp-luc fusion gene under the control of the schizontspecific ama1 promoter integrated into the silent 230p gene locus (PBANKA_0306000) and does not contain a drug-selectable marker (21), was used to obtain P. berghei-VAR. P. berghei ANKA-GFP-Luc (1037cl1) parasites (P. berghei) were also used in all experiments.…”
Section: Methodsmentioning
confidence: 99%